An evaluation of WIL training for Durban University OF Technology Civil Engineering ‒ employer and student experience: Lessons for the new programme - Khuzwayo, B. P.; Vahed, S. (South African Journal of Higher Education, 2021)
The Durban University of Technology (DUT) previously offered the now phased-out National Diploma in Civil Engineering, incorporating a two-year academic enrolment and a year-long work-integrated learning programme (WIL). The support offered by the University lecturers was essential in the WIL, to ensure that the engineering tasks assigned to students aligned with the DUT curriculum; any concerns or comments expressed were investigated further and addressed appropriately. In 2017 and 2018 interviews were conducted, generating 918 structured comments by employers. These included 304 general comments (with no academic value) and 593 comments specific to disciplines by students, of which 346 were general comments. This exploratory study aims to determine critical feedback that should be considered when enrolling for the new qualification: Bachelor of Engineering Technology Degree in Civil Engineering (B Eng Tech degree). The data received helped to discover and understand the experiences, perspectives and thoughts of the participants who responded to open-ended questions (i.e., comments about their experiences, without any limitations). The data collected were presented and evaluated using the thematic analysis method to discover patterns and to develop subjects for discussion. Findings show that employers were generally happy with the quality of the students from DUT, however, they found professionalism among the DUT students to be a major concern. They also requested that the institution communicates with employers regarding the curriculum so that employers might properly align the WIL with it. Most students were challenged by the new work environment they had entered. The most common factor that made the experience more challenging was the exposure to the state-of-the-art equipment used in the workplace.